Effects of urbanization on economic growth and human capital formation in Africa - (:unkn) unknown (My University, 2014)
The objective of this paper is to investigate the impacts of urbanization on human capital andeconomic growth in Africa. It seeks to contribute to the urbanization-growth debate byinvestigating how urbanization is linked to human capital accumulation and economic growth.More precisely, compared to previous studies on the urbanization-growth nexus, we (i) focusexclusively on African countries; (ii) consider both direct and indirect channels through whichurbanization may influence economic activity and (iii) examine a long period including theevolutions observed in the recent years.
Keywords: African Research